2023
DOI: 10.1097/hc9.0000000000000234
|View full text |Cite
|
Sign up to set email alerts
|

Overview and prospect of NAFLD: Significant roles of nutrients and dietary patterns in its progression or prevention

Tianyu Mao,
Yiwen Sun,
Xinyi Xu
et al.

Abstract: NAFLD is the most common chronic liver disease worldwide, characterized by lipid accumulation in the liver, and usually evolves from steatohepatitis to fibrosis, cirrhosis, or even HCC. Its incidence is rapidly rising in parallel with the increasing prevalence of obesity and metabolic syndrome. Current therapies are limited to lifestyle changes including dietary intervention and exercise, in which dietary modification exerts an important part in losing weight and preventing NAFLD. In this review, we briefly di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 318 publications
0
4
0
Order By: Relevance
“…Common recommendations include eliminating excess carbohydrates in favor of whole foods. 6,16,17 This strategy is challenged in the context of increasingly prevalent food insecurity. In this nationally representative study, we showed that food insecurity was prevalent among those with liver disease, and their levels increased signi cantly over time.…”
Section: Discussionmentioning
confidence: 99%
“…Common recommendations include eliminating excess carbohydrates in favor of whole foods. 6,16,17 This strategy is challenged in the context of increasingly prevalent food insecurity. In this nationally representative study, we showed that food insecurity was prevalent among those with liver disease, and their levels increased signi cantly over time.…”
Section: Discussionmentioning
confidence: 99%
“…While vegetables are generally considered low-carbohydrate foods and those with high dietary fiber levels may reduce the risk of NAFLD (33), excessive intake of starchy vegetables might increase blood glucose and insulin resistance, which is detrimental to NAFLD patients (53). Similarly, fruits contain natural fructose, and high fructose intake increases hepatic de novo lipogenesis (DNL), reduces fatty acid β-oxidation (FAO), and leads to fatty acid deposition (54). Excessive fructose intake can also promote the development of NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that dietary patterns and nutrient compositions have significant impacts in promoting or counteracting the development and progression of MASLD [ 52 ]. Moreover, the heterogeneity of gut microbial composition can be modulated positively or negatively by different dietary patterns [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the impact of high protein consumption on MASLD, little is known, as most reports focus on carbohydrates and fats. Moreover, the role of a meat-based diet in MASLD development remains controversial, depending on the type and amount of protein intake [ 52 ]. Despite this inconclusive data, an unhealthy Western diet with a high protein intake is thought to be related to the increased prevalence and severity of MASLD [ 53 ].…”
Section: Discussionmentioning
confidence: 99%